The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/jso.24575
|View full text |Cite
|
Sign up to set email alerts
|

A proposal of post‐operative nomogram for overall survival in patients with renal cell carcinoma and venous tumor thrombus

Abstract: For patients with RCC and VTT, the developed and internally validated post-operative nomogram can be used to select patients who may benefit from aggressive surveillance regimens or adjuvant therapy clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
(57 reference statements)
0
21
1
1
Order By: Relevance
“…In the tumor stage subgroups, Katkoori et al showed that right‐sided RCC was associated with a higher ratio of level III inferior vena cava (IVC) tumor thrombus (T3b) patients than with left‐sided RCC. Other reports have shown incidence rates of right‐sided IVC tumor thrombus of 53.5%, 64% and 81% . Conversely, fewer patients had stage T3b disease on the right side than on the left side in this study.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…In the tumor stage subgroups, Katkoori et al showed that right‐sided RCC was associated with a higher ratio of level III inferior vena cava (IVC) tumor thrombus (T3b) patients than with left‐sided RCC. Other reports have shown incidence rates of right‐sided IVC tumor thrombus of 53.5%, 64% and 81% . Conversely, fewer patients had stage T3b disease on the right side than on the left side in this study.…”
Section: Discussioncontrasting
confidence: 49%
“…Other reports have shown incidence rates of right-sided IVC tumor thrombus of 53.5%, 64% and 81%. [14][15][16] Conversely, fewer patients had stage T3b disease on the right side than on the left side in this study. A similar trend was observed for stage T4, lymph node and organ metastasis RCC patients.…”
Section: Discussionmentioning
confidence: 56%
“…Initially identi ed 267 articles through the search strategy, 19 studies remained after removing duplicates and excluding articles by viewing titles and abstracts. Based on corresponding inclusion and exclusion criteria, 8 articles comprising 5,025 patients were nally included in the present study [14,15,[18][19][20][21][22][23] ( Figure 1). All studies had a retrospective design, two of which were propensity score-matched analyses.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…3 studies focused on metastatic RCC [19,21,22], 5 studies focused on non-metastatic RCC [14,15,18,20,23]. These studies were conducted in ve countries, including China, Korea, Turkey, Japan, and the United States.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation